PTH-124 Liver transplant outcomes in patients with care devolved to a non-transplanting centre: south west liver unit experience. (22nd June 2015) - Norton, BC; Adebayo, D; Ramos, K; Smith, A; Cramp, M
Abstract : Introduction: With only seven transplant centres currently commissioned in the UK, many patients travel long distances for specialist care. A hepatology network was established with the support of King's College Hospital in the South West Peninsula 13 years ago. Over time a devolved model of assessment and care for liver transplant patients, involving a large regional centre and referring hospitals, has been developed with post-transplant care delivered close to the patients' home. Our aim is to establish whether patients receiving care at the South West Liver Unit have similar outcomes to current transplant centres. Method: We retrospectively analysed data of all potential liver transplant patients cared for at the South West Liver Unit between 2000–2015. We created a patient database by reviewing clinical documents, which included all 361 patients formally assessed for liver transplant at the South West Liver Unit, and 174 patients who have undergone transplantation to date. Of the cases transplanted since the network was established, 21 received a transplant since 1 st March 2014 and 153 over 1 year ago. Where a patient was re-transplanted the most recent transplant date was used. We undertook a survival analysis using a Kaplan-Meier survival plot on SPSS V.20 to determine percentage survival at 1, 3, and 5 years post-transplantation. Results: The median survival time post-transplantation in our patient group was 12.6 years (95% confidence intervals 11.6–13.5). In total, 23 of the 174 patients died during follow up. Survival analysis (Figure 1) demonstrated non-risk adjusted survival rates of 93.4%, 92.7%, and 85.4% at 1, 3, and 5 years, respectively. These results are concordant with those currently reported by the seven transplant units within the UK. Conclusion: The 1, 3, and 5 year survival outcomes for liver transplant recipients whose post-transplant care was provided by a non-transplanting centre and its network, are good and comparable to those of all current transplant centres. With increasing numbers of patients being transplanted and surviving, provision of accessible specialist care is becoming increasingly important. This data provides reassurance that devolution of care of liver transplant recipients, to appropriately staffed and trained regional centres, is a viable model for service delivery. Centres demonstrating good post-transplant outcomes will be well placed to develop into transplant units in the future. Disclosure of interest: None Declared.